Preservation effect of plant essential oil-KGM composite coating materials on the tomatoes - Jianming Sun; Linlin Li; Xiao Pan; Yini Yao; Tiantian Wang; Hui Liu; Lei Liu; Zhao Li; Xiaofang Wang (PLoS ONE, 2025)
Tomatoes with rich in nutrients are very popular for humans, but they are extremely perishable during storage and transportation, which may limit their economic and nutritional value. In this research, the suitable concentration of essential oil and soaking time were investigated and selected by measuring the changes of tomatoes’ weight loss ratio and hardness with single factor experiment. Subsequently, the Box-Behnken experimental design model from Response Surface Methodology (RSM) was employed to optimize key process parameters for tomato preservation, with three independent variables selected: cinnamon essential oil concentration, konjac glucomannan (KGM) concentration, and immersion time. As a result, cinnamon essential oil with good preservation effect was selected and combined with KGM to prepare coating materials for the preservation of tomatoes. The optimized preservation condition for tomatoes was in a solution with 0.70 g/L cinnamon essential oil, 8.20 g/L KGM and soaking time for 3.2 min, which had a good preservation effect on tomatoes with 2.5% weight loss ratio and 1.3% hardness after 10 days at room temperature, reduced the consumption of total soluble solid (TSS), delayed the decline of vitamin C (Vc) content, inhibited the increase of malondialdehyde (MDA) content, and enhanced peroxidase (POD) activity. This study demonstrates that the composite coating combines synergistic barrier properties, dual functionality, and economic advantages, establishing a theoretical framework for sustainable tomato preservation while providing transferable strategies for other produce.